Exploring Discovery Learning Using Cue Card to Enhance Interpersonal and Transactional Text Teaching at SMKN Tapango : A Classroom Action Research - Styana Ika Wahyuni; Sukardi Weda; Andi Anto Patak (International Journal of Language, Education, and Literature, 2025)
This research aims to explore the effectiveness of discovery learning using cue cards in enhancing the teaching of interpersonal and transactional texts at SMK N Tapango. Conducted as Classroom Action Research (CAR) from April to June 2024, the study involved 35 students of class X DKV A. The research was implemented over two cycles, with each cycle comprising stages of planning, action, observation, and reflection. Data were collected through a combination of document, observations and were analyzed using both qualitative and quantitative methods to assess the progress and effectiveness of the learning strategy. The results demonstrated a significant improvement in the students' understanding and application of interpersonal and transactional texts. The use of cue cards in the discovery learning model proved to be highly effective, as evidenced by the increase in average student scores from the pre-cycle diagnostic assessment to the final cycle, rising from an average score of 58.8% to 85.2%. These findings underscore the potential of discovery learning with cue cards as a powerful tool in engaging students and enhancing their communication skills in vocational high school settings.